Framing Pemberitaan Calon Presiden 2024 Ganjar Pranowo pada Media Alternatif Perempuan Konde.co dan Magdalene.co - Guntur Siberson; Filosa Gita Sukmono (Indonesian Scientific Journal (Jurnal Ilmiah Indonesia), 2025)
The media has become a strategic tool in the 2024 election contest to build political image. Presidential candidates utilize positive coverage and media strategies to increase popularity and shape the desired public perception. Despite Ganjar's high electability, he often finds himself entangled in controversial blunders. This study examines how konde.co and magdalene.co, as alternative women's media, frame Ganjar Pranowo's political agenda. The research aims to understand the framing of Ganjar Pranowo's news coverage as a 2024 presidential candidate on the konde.co and magdalene.co news portals. The method used is qualitative, employing Zhongdang Pan and M. Gerald Kosicki's framing analysis, which considers four text structure devices: syntactical, script, thematic, and rhetorical. The results show that konde.co frames Ganjar Pranowo with rhetoric focusing on portraying him as a potential leader who brings positive change. On the other hand, magdalene.co modifies the style of reporting on Ganjar Pranowo during the pre-campaign, campaign, and post-campaign periods. The chosen diction often aims to provoke critical thinking among readers and highlight contradictions in Ganjar's policies and actions.. Keywords: Ganjar Pranowo, Framing, Women's alternative media, Election 2024